FEATURES OF THE ORGANIZATION OF EDUСATIONAL PROCESS IN SOVIET HIGHER SCHOOL - Alina I. Timirgazieva (Moscow Polytechnic University, 2016)
The article addresses to the archival materials of the Republic of Bashkortostan illustrating the organization of the educational process in higher educational institutions of the Soviet period, assesses the development of teaching methods, scientific and educational work. Particular attention is paid to the influence of the existing regime on educational activities of the departments of social sciences and humanities. This article will be interesting for professionals involved in the history of education.